GaN-based Double-hetero Film Grown and Fabricated on (0001) Sapphire Substrates by Plasma-assisted MOCVD - Heri Sutanto; Edi Supriyanto; Maman Budiman; Pepen Arifin; Sukirno Sukirno; Mohamad Barmawi (Jurnal Matematika & Sains, 2005)
GaN-based double-hetero film has been grown on (0001) sapphire substrate by plasma-assisted MOCVD method. The structure of film was n-GaN/Al0.25Ga0.75N/In0.3Ga0.7N/Al0.25Ga0.75N/p-GaN. A photoluminescence (PL) peak originating from InGaN active layer has been observed at room temperature, which produced emission wavelength of 453 nm corresponded to energy of 2.74 eV. However, broadening of the peak caused by the crystalline quality of the InGaN epilayer is still poor, which is related with fluctuation of In rich regions.